2018
DOI: 10.1007/s00360-018-1151-8
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the recombinant crustacean hyperglycemic hormones rCHH-B1 and rCHH-B2 on the osmo-ionic regulation of the shrimp Litopenaeus vannamei exposed to acute salinity stress

Abstract: The Pacific white shrimp Litopenaeus vannamei is a euryhaline organism that copes with salinity fluctuations in the environment; therefore, its osmotic and ionic regulation abilities are vital. Osmoregulation may be controlled by the crustacean hyperglycemic hormone (CHH), a neuropeptide mainly expressed in the eyestalks. In L. vannamei, CHH-B1 and CHH-B2 are CHH isoforms isolated from the eyestalks whose expression is influenced by environmental salinity. It has been suggested that they are involved in the re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
19
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 87 publications
2
19
4
Order By: Relevance
“…In the present work, a significant increase in haemolymph glucose levels (40%–60%) was observed at 0.5 hr and 1 hr post‐injection of rCHH‐B2 in comparison with the rCHH‐B1 levels. A higher hyperglycemic activity has also been obtained with the rCHH‐B2 during isosmotic conditions (26 ppm), but not on the shrimp acutely exposed to hypo‐osmotic (8 ppm) or hyper‐osmotic salinities (45 ppm) (Camacho‐Jiménez et al., 2018). Furthermore, glucose analysis of haemolymph of shrimp injected with dopamine (DA) suggested that the hyperglycemic effect of DA is mediated by the release of CHH neuropeptides from the eyestalk of L. vannamei (Camacho‐Jiménez, Díaz, et al, 2017).…”
Section: Discussionmentioning
confidence: 96%
See 4 more Smart Citations
“…In the present work, a significant increase in haemolymph glucose levels (40%–60%) was observed at 0.5 hr and 1 hr post‐injection of rCHH‐B2 in comparison with the rCHH‐B1 levels. A higher hyperglycemic activity has also been obtained with the rCHH‐B2 during isosmotic conditions (26 ppm), but not on the shrimp acutely exposed to hypo‐osmotic (8 ppm) or hyper‐osmotic salinities (45 ppm) (Camacho‐Jiménez et al., 2018). Furthermore, glucose analysis of haemolymph of shrimp injected with dopamine (DA) suggested that the hyperglycemic effect of DA is mediated by the release of CHH neuropeptides from the eyestalk of L. vannamei (Camacho‐Jiménez, Díaz, et al, 2017).…”
Section: Discussionmentioning
confidence: 96%
“…The functional diversity of CHHs has been related to variants differing in sequence and structures within species (Lee et al., 2014). Three different CHH variants have been cloned and sequenced by our group from the Pacific white shrimp L. vannamei : CHH‐A, CHH‐B1 and CHH‐B2 (Camacho‐Jiménez et al., 2015, 2018; Camacho‐Jiménez, Sánchez‐Castrejón, et al, 2017; Lago‐Lestón et al., 2007; Sanchez‐Castrejón, Ponce‐Rivas, Aguilar, & Díaz, 2008). Additionally, a new gene containing four exons and three introns was isolated from L. vannamei (Ventura‐López et al., 2016).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations